Synthesis and biological evaluation of some new heterocyclic derivatives from substituted thiopyrimidine - Aziz Hadil S.; Al-Araj Intisar Q.M.; Abdul-Raheem Linda R.; Ahmed Amena A. (Journal of the Serbian Chemical Society)
This study aimed at creation of a few new heterocyclic compounds that include sulfur and nitrogen atoms. Also, some chalcones, thiazolidine and Schiff base derivatives have been prepared. The spectroscopic data (IR, 1Hand 13C-NMR) have verified the structure of the produced molecules. Interesting findings were obtained when several synthetic substances were physiologically tested against a range of pathogenic Gram-positive and Gram-negative bacteria.